Reforçamento específico em treino de discriminações condicionais e teste de simetria com um macaco-prego (Cebus apella) - KATAOKA, Katarina Bonfim (2008)
It is possible that organisms have a basic relational capacity. Therefore, equivalence relations would be generated by the reinforcing contingencies. Inconsistent outcomes obtained in test of equivalence class formation would be due to experimental procedures of training and testing that are not capable to generate the performance planned. Building on the assumption that not only the discriminative stimuli, but also the response and reinforcers, if specific to each class, become members of the class, this study aimed to evaluate the performance of a capuchin-monkey (Cebus apella) with pre-experimental history in condicional discriminations and use of the blank comparison (mask), in tests of symmetry BA after training with specific reinforcement, pellets of food of the diferent flavors for each discrimination. During training, blank comparisons substituting S+ and Swere used, to assure controlling relations consistent with planned. After training, it was tested the symmetric relations, also with specific reinforcing, the outcome was inconsistent with the formation of classes. It is possible that more training sessions with specific. Reinforcement would be necessary, and/or the similarities between reinforcers of each class have allowed generalization between them.